SERVICE QUALITY, BANKING SERVICE TO WARDS BANKING DEVELOPMENT - Akbar Jaya (JOURNAL OF SHARIA ECONOMICS, 2023)
The development of Sharia Banks in Papua is currently considered good, this is marked by the existence of Bank Syariah Mandiri and Bank Muamalat. However, existing sharia banks are not yet in great demand by customers because there is tight competition between sharia banks and conventional banks in Papua, especially Keerom Regency. This research was conducted in Keerom Regency, Papua Province, while the research was carried out from April to June. The type of research used is qualitative and quantitative research. Service quality is 3.505. The size of the ttable at α = 0.05 is 1.675. The tcount for service quality is 3.505 > from ttable 1.675 with a significance figure of 0.001 < 0.05. Thus, it can be concluded that service quality has a significant positive effect on banking development. Banking services have a significant positive effect on banking development. This result can be seen in the t test which has tcount = 2.906 > from ttable 1.675 with a significant number of 0.006. Thus, it can be concluded that banking services have a significant positive effect on banking development. Based on the results of the F test analysis, it shows that the F¬count is 18.358 and the F¬table value is 3.18 or (18.358 > 3.18) with a sig of 0.000 0.05, it can be concluded that together (simultaneously) there is significant influence between service quality (X1) and banking services (X2) on banking development (Y). This shows that if simultaneously the quality of banking services increases, it will have an impact on increasing banking development and vice versa.